KAJIAN DISTRIBUSI SUHU PERMUKAAN LAUT DAN KLOROFIL–A DI PERAIRAN ACEH BARAT - Willy Okta Fianda; Mai Suriani (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
West Aceh is an area that is directly opposite the Indian Ocean and has its own Oceanographic characteristics and dynamics. Sea surface temperature and chlorophyll-a are influenced by these oceanographic factors, such as currents and winds. wind, besides that the fertility of a water body is closely related to temperature and chlorophyll-a. The purpose of this study was to determine the distribution pattern of sea surface temperature sea surface temperature and chlorophyll-a and determine the relationship between sea surface temperature and chlorophyll-a in the waters of the ocean. and chlorophyll-a in the waters of West Aceh. This research was conducted from January to October 2022 in the waters of West Aceh. The method used descriptive method and mathematical modeling method. Observation results It was found that the distribution pattern of sea surface temperature has a difference every month. the lowest temperature in October 29.150C and the highest in May 35.090C. May 35.090C. Distributed temperature distribution caused by by the movement of currents and winds on the sea surface. high chlorophyll-a concentrations are close to the mouth of the river around the West Aceh coast and are distributed by currents and surface winds. range of chlorophyll concentration concentrations were lowest in August at 0.09 mg/m3 and highest in September at 6.97 mg/m3. September 6.97 mg/m3. The correlation coefficient (r) of the relationship between sea surface temperature and chlorophyll-a of 0.601797 which is positive